Implementasi Konsep Pemeliharaan Mesin untuk Peningkatan Produktivitas dalam Dunia Industri - Muhammad Ardi; Rizky Sulvika Puspa Rinda; Samen Lolongan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: Maintenance plays a crucial role in the industrial sector to maintain and restore the optimal performance of machinery and equipment. This activity, conducted as a community service for mechanical engineering students, aims to provide an initial understanding of maintenance concepts and strategies as a preparation for entering the workforce. Methodology/approach: The program used interactive lectures, presentations, discussions, and case studies covering breakdown, corrective, preventive, predictive, and reliability-centered maintenance topics. It also introduced the DMAIC steps (Define, Measure, Analyze, Improve, Control) and the link between maintenance, productivity, and industrial processes. Results: The program improved students’ understanding of basic maintenance concepts, asset management strategies, and the importance of maintenance for smooth production and safety. Students were also able to identify critical factors in maintenance management, such as machines, materials, methods, manpower, and the environment. Conclusions: The seminar effectively increased students’ knowledge and readiness to face the challenges of the workplace. A solid foundation of maintenance concepts enhances efficiency, productivity, and competitiveness in the industry. Limitations: The study was limited to one group of students and short-term training; therefore, further studies involving larger samples and longitudinal evaluations are recommended. Contributions: This program provides practical and theoretical insights, supporting the development of future workers with strong analytical and problem-solving skills in maintenance engineering.